Enhanced Photo-Catalytic Degradation of MB Dye over Hydrothermal Grown-Up of ZnO/SnO2 Catalyst - Govinda Dharmana; Santhosh Kumar Nadikatla; Thirumala Rao Gurugubelli; Balaga Viswanadham (Journal of Chemistry)
In this work, pure ZnO, SnO2, and ZnO-SnO2 nanostructured composites (Z-S heterostructure) are fabricated by a facile and environmental savvy hydrothermal method at 230°C for 12 hours and followed by high-temperature annealing. The synthesized samples were examined to analyse the structural and optical characteristics using XRD, TEM, XPS, and UV-DRS techniques. Investigate the photocatalytic activity (PCA) of pure ZnO, SnO2, and Z-S heterostructure for the decolorization of methylene blue (MB) model pollutant in wastewater using visible light irradiation. XRD analysis reveals that ZnO and SnO2 exhibit hexagonal wurtzite structure and tetragonal rutile structure. TEM micrographs infer the nanorod-like structure of ZnO, nanoflake-like structure of SnO2, and a thin nanosheet-like structure of Z-S. XPS analysis evidence for the presence of constitutes elements and Zn+2, Sn+2, O−2 valance states along with environmental peaks in Z-S heterostructure. The optical band gaps of ZnO (3.37 eV), SnO2 (3.6 eV), and Z-S heterostructure (2.84 eV) are inferred by UV-DRS analysis, together with evidence for the red shift. Under two hours of visible light illumination, the photocatalytic degradation efficiency of MB dye in pure ZnO, SnO2, and Z-S heterostructure is 38.55, 32.68, and 82.45%. The formation of a unique Z-S heterostructure and the maximum departure of charge carriers are the reasons for obtaining robust degradation activity than pristine ZnO and SnO2. MB dye degradation process in the presence of Z-S heterostructure photocatalyst, the reusability test findings, and the suggested charge separation technique for customizing Z-S heterostructure photocatalyst under visible light irradiation is presented.